2017
DOI: 10.1002/jhet.2988
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antimicrobial Activity of 2‐(4‐(Hydroxyalkyl)‐1H‐1,2,3‐triazol‐1‐yl)‐N‐substituted propanamides

Abstract: A series of 21 2‐(4‐(hydroxyalkyl)‐1H‐1,2,3‐triazol‐1‐yl)‐N‐substituted propanamides (1,4‐disubstituted 1,2,3‐triazoles having amide linkage and hydroxyl group) have been synthesized from click reaction between terminal alkyne and 2‐azido‐N‐substituted propanamide (generated in situ from reaction of 2‐bromo‐N‐substituted propanamide and sodium azide) and characterized by FTIR, 1H NMR, 13C NMR spectroscopy, and HRMS. All the newly synthesized triazoles were tested in vitro for antimicrobial activity against fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…All the compounds were tested for antibacterial activity against Bacillus cereus (MTCC 430), Staphylococcus aureus (MTCC 3160), and Escherichia coli (MTCC 443) by employing serial dilution method . Minimum inhibitory concentrations were expressed in μmol/mL as represented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the compounds were tested for antibacterial activity against Bacillus cereus (MTCC 430), Staphylococcus aureus (MTCC 3160), and Escherichia coli (MTCC 443) by employing serial dilution method . Minimum inhibitory concentrations were expressed in μmol/mL as represented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In vitro antibacterial activity of all the compounds ( 7a ‐ 7o ) was carried out against bacteria— B. cereus, S. aureus , and E. coli by standard serial dilution method . A stock solution of 200 μg/mL concentrations in for all the compounds was used which, further serially diluted to get concentration of 100, 50, 25, 12.5, 6.25 μg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…Bazı Yeni 1,2,3-Triazol-arilidenhidrazid Hibrit Bileşiklerinin Sentezi ve Anti-mikrobiyal Etkinliklerinin Belirlenmesi Triazoller, üç azot ve iki karbon atomu taşıyan beş üyeli halka yapısında ve geniş kapsamlı biyolojik akviteleri ile öne çıkan heterosiklik organik bileşiklerdir. Literatüre bakıldığında 1,2,3-triazol halkası taşıyan bileşiklerin geçmiş yıllardan beridir başlıca antienflamatuvar, antikanser, antiromatizmal ve antimikrobiyal etkiler gösterdiği yapılan çalışmalardan görülmektedir (Frutos ve ark., 2014;Subhashini ve ark., 2014;Krolenko ve ark., 2016;Lal ve ark., 2016;Kaushik ve Luxmi, 2017;Jain ve ark., 2018;Kaushik ve ark., 2018;Liu ve ark., 2018;Kumar ve ark., 2019;van Hilst ve ark., 2019;Aparna ve ark., 2020;Cardoso ve ark., 2020;Kumar ve ark., 2021). 1,2,3-triazol yapısı taşıyan 1-8 numaralı ilaç molekülleri bu bileşiklere örnek olarak verilebilir.…”
Section: (1) 468-481 2023unclassified
“…Structure-activity relationship revealed that phenyl ring with electronegative bromo substitution at para position next to amide group proved to be display good antifungal activity, whereas other substitutions like naphthyl rings or phenyl ring with nitro or chlorine group at the para position did not elevate the potential. [38] Similarly, Phatak et al synthesised a series of molecules containing acetylphenoxymethyl, triazole and N-phenylacetamide moieties. The compounds were screened for their antifungal activity against Candida albicans.…”
Section: 23-triazole Derivatives With Antifungal Activity Against As ...mentioning
confidence: 99%